Key technology of VANET in terminal-management-cloud model - Junhui ZHAO; Yan CHEN; Dechang HUANG; Dacheng HUANG (Dianxin kexue)
With the increasing of traffic problems，such as traffic congestion，intelligent transportation system（ITS）becomes an effective way to solve the increasing transportation issues of the current traffic.Vehicular Ad Hoc networks（VANET）and vehicles as important parts of ITS have become focus of current research.Firstly，the development history and current situation of VANET both at home and abroad were introduced，and then VANET from the terminal system，management system，cloud system were analyzed respectively.Then，the V2V and V2R communication technologies of terminal system were introduced emphatically.In addition，VANET oriented traffic cloud and big data technology were outlined.Finally，application scenarios and the future development of communication technologies in VANET were discussed.